Short-term reaction of stock markets to a new mechanism: the case of Shanghai-Hong Kong Stock Connect - Chow, Yan Pang, Darien (2015)
While taking a gradualist approach in financial liberalization, China announced a “Through Train” in Tianjin as the first stock market liberalization measure at individual investor level in August 2007, which surprised the market but was set aside eventually. Finally after 7 years, a new measure of similar nature, the Shanghai-Hong Kong (SHHK) Stock Connect has been announced on 10 April 2014 and implemented on 17 November 2014. Although stakeholders emphasize on the mutual benefits of this new system, stock market liberalization measures are expected to be implemented by China after the “Through Train” in 2007. Based on the Efficient Market Hypothesis, the market has already reacted to all the available information through stock prices.